2013
DOI: 10.5897/ajmr2012.2390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial activity of Laurus nobilis L., Rosmarinus officinalis L. and Ocimum basilicum L. from Northeast of Algeria

Abstract: Rosmarinus officinalis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The sensitivity of microorganisms may vary according to the germ tested because an essential oil may be bactericidal with respect to certain strains, bacteriostatic with respect to others or have no effect [19]. Previous studies on the essential oil of Rosmarinus officinalis reveal antimicrobial activity and indicate a similarity with the results obtained in this work [23,26,13,24,20,5]. Gram-bacteria are more resistant than Gram +, this is due to the structural differences of their outer membranes as advanced by [7].…”
Section: Discussionsupporting
confidence: 76%
“…The sensitivity of microorganisms may vary according to the germ tested because an essential oil may be bactericidal with respect to certain strains, bacteriostatic with respect to others or have no effect [19]. Previous studies on the essential oil of Rosmarinus officinalis reveal antimicrobial activity and indicate a similarity with the results obtained in this work [23,26,13,24,20,5]. Gram-bacteria are more resistant than Gram +, this is due to the structural differences of their outer membranes as advanced by [7].…”
Section: Discussionsupporting
confidence: 76%
“…In the study conducted by us, it was determined that essential oils of laurel (31.75 mm), rosemary (30.5 mm), and coriander (20.50 mm) had strong antimicrobial effect; basil essential oil (14.25 mm) had strong medium antimicrobial effect. Ouibrahim et al (2013) reported that the inhibition zones against 20 bacteria they tested were 8.4-22.4 mm for laurel; 8.4-16.4 mm…”
Section: Antibacterial Effect Of Essential Oilsmentioning
confidence: 99%
“…It is known that the effect of essential oils in the control of pathogenic microorganisms in foods is very important and there are many researches on this subject (Abdollahzadeh et al, 2014;Azeredo et al, 2011;Da Silveira et al, 2014;De Medeiros Barbosa et al, 2016;Dussault et al, 2014;Ghabraie et al, 2016;Gill et al, 2002;Gutierrez et al, 2008;Khalil et al, 2018;Mazzarrino et al, 2015;Ouibrahim et al, 2013;Pesavento et al, 2015;Tosun et al, 2018). However, only a few studies have been performed on the use of essential oils on the inactivation of L. monocytogenes, which is a significant problem in foods that are ready-to-eat products and processed at low temperatures-times with sous-vide application (Gouveia et al, 2016(Gouveia et al, , 2017.…”
mentioning
confidence: 99%
“…Same results found by Ghazi (2013) and Verma et al (2013) opposite of those found by (Imelouane et al, 2009a). The synergy between terpenes (linalool), oxides (1,8 cineole) and monoterpenes (camphene, α-pinene) gives to the essential oil of Laurel a good antibacterial activity (Ouibrahim et al, 2013). The major components of this oil, 1.8-cineole, have been known to exhibit antimicrobial activity against the bacterial strains (E. Coli, P. Aeruginosa, S. Typhi, S. Aurus, Rhizobium leguminosarum and Bacillus subtilis) (Sivropoulou et al, 1997).…”
Section: Antimicrobial Activitymentioning
confidence: 99%